Interpersonal Communication Model on Parenting with Adolescent - Sa'diyah, Elok Halimatus; Hidayati, Fina; Melinda, Vannissa Aviana (Journal An-Nafs: Kajian Penelitian Psikologi, 2023)
The role of parents becomes relational reframing for adolescents; with all the turmoil and characteristics that adolescents have, communication between parents and adolescents is the key to success in the parenting process. This study aims to prove the interpersonal models of parents-adolescents who are influenced by self-compassion and self-disclosure, either directly or indirectly. The method of this study is a quantitative correlation, with the sampling technique purposive sampling. The participants of the study numbered 287 parents, consisting of 98 fathers and 189 mothers. The instruments used are ICS (Interpersonal Communication Scale) by Campbell (2006), SCS (Self-Compassion Scale) by Neff (2003), and Self-Disclosure Scale by Whells & Grotz (1997). The analysis showed that the interpersonal communication model was proven to influence self-compassion and self-disclosure directly. However, self-disclosure does not prove to be a mediator variable between self-compassion and interpersonal communication. The score showed that self-compassion - interpersonal communication had an influence of Î² = 0.399 (39.9%) with p = 0.000, and self-disclosure - interpersonal communication had an influence of Î² = 0.282 (28.2%) with p = 0.007. The demographic analysis also found that fathers have higher self-compassion than mothers. At the educational level, it also shows differences in the level of interpersonal communication skills, self-compassion, and self-disclosure.